Compliance with Follow‐up and Adherence to Medication in Hypertensive Patients in an Urban Informal Settlement in Kenya: Comparison of Three Models of Care - Ng’endo, Kuria; Anthony, Reid; Philip, Owiti; Hannock, Tweya; Kibet, Caleb Kipkurui; Mbau, Lilian; Marcel, Manzi; Victor, Murunga; Tecla, Namusonge; Joseph, Kibachio (ResearchGate, 2018)
objective To determine and compare, among three models of care, compliance with scheduledclinic appointments and adherence to antihypertensive medication of patients in an informalsettlement of Kibera, Kenya.methods Routinely collected patient data were used from three health facilities, six walkway clinicsand one weekend/church clinic. Patients were eligible if they had received hypertension care for morethan 6 months. Compliance with clinic appointments and self-reported adherence to medication weredetermined from clinic records and compared using the chi-square test. Univariate and multivariatelogistic regression models estimated the odds of overall adherence to medication.results A total of 785 patients received hypertension treatment eligible for analysis, of whom two-thirds were women. Between them, there were 5879 clinic visits with an overall compliance withappointments of 63%. Compliance was high in the health facilities and walkway clinics, but menwere more likely to attend the weekend/church clinics. Self-reported adherence to medication bythose complying with scheduled clinic visits was 94%. Patients in the walkway clinics were two timesmore likely to adhere to antihypertensive medication than patients at the health facility (OR 1.97,95% CI 1.25–3.10).conclusion Walkway clinics outperformed health facilities and weekend clinics. The use ofmultiple sites for the management of hypertensive patients led to good compliance with scheduledclinic visits and very good self-reported adherence to medication in a low-resource setting.
© 2018 The Authors. Tropical Medicine & International Health Published by John Wiley & Sons Ltd. 785This is an open access article under the terms of the Creative Commons Attribution License, which permits use,distribution and reproduction in any medium, provided the original work is properly cited.
Keywords: Hypertension; Models of care; Walkway clinics; Weekend clinics; Medical management; Operational research